2007
DOI: 10.1186/1472-6963-7-199
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admission patterns subsequent to diagnosis of type 1 diabetes in children : a systematic review

Abstract: Background: Patients with type 1 diabetes are known to have a higher hospital admission rate than the underlying population and may also be admitted for procedures that would normally be carried out on a day surgery basis for non-diabetics. Emergency admission rates have sometimes been used as indicators of quality of diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 40 publications
3
40
1
Order By: Relevance
“…Although a higher hospital admission rate in pediatric subjects with T1D compared to that without T1D was also reported in other studies, the OR in our study population were considerably higher . A study from the German/Austrian DPV registry reported a 3‐fold higher admission rate ratio compared to the general pediatric population without T1D .…”
Section: Discussioncontrasting
confidence: 56%
“…Although a higher hospital admission rate in pediatric subjects with T1D compared to that without T1D was also reported in other studies, the OR in our study population were considerably higher . A study from the German/Austrian DPV registry reported a 3‐fold higher admission rate ratio compared to the general pediatric population without T1D .…”
Section: Discussioncontrasting
confidence: 56%
“…The Hvidøre study found higher A1C in girls (7), but others studies did not (8,9). Adolescent girls have more ketoacidosis (10,11), but overall the sex difference is minimal. In 2006 more insulin was prescribed in proportion to children being heavier.…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review of 32 publications on hospital admission patterns found that patients with type 1 diabetes are 3 times more likely to be hospitalized than nondiabetic populations 7. Although standards of diabetes care in youth have improved since the Diabetes Control and Complications Trial,4 rates of rehospitalization have not followed the same trend.…”
mentioning
confidence: 99%